Development of conceptual model of the cluster association of agricultural enterprises project - Тимочко, Василь Олегович; Ковальчик, Юрій Іванович; Говда, Оксана Ігорівна; Падюка, Роман Іванович (Eastern-European Journal of Enterprise Technologies, 2012)
The expedience of introduction the innovative technologies on the base of cooperative use of technical facilities are grounded in the article. The stages of the conceptual model working out of the project cluster association of agricultural enterprises are defined